Effect of graded nursing based on the Glasgow-Blatchford score in liver cirrhosis patients complicated with acute upper gastrointestinal bleeding - Liu, Mingshu; Wang, Haifang; Shao, Fei; Xu, Yanfang; Huang, Jing; Zhang, Huijie; Han, Yaru (Frontiers in Medicine, 2025)
AimTo study the effect of graded nursing based on the Glasgow-Blatchford score in liver cirrhosis patients complicated with acute upper gastrointestinal bleeding (AUGIB).MethodsFrom January 2022 to December 2024, eighty patients with liver cirrhosis complicated with AUGIB treated in our hospital were chosen and separated into control group and study group. The control group received routine nursing, and the study group received graded nursing based on the Glasgow-Blatchford score. The hemostatic time and hospital stay, number of patients with re-bleeding and death, Glasgow-Blatchford score, incidence of complications, psychological states, self-care ability, quality of life and nursing satisfaction were compared between the two groups.ResultsCompared to the control group, the study group had shorter hemostatic time and hospital stay, lower rate of re-bleeding and death, lower incidence of complications and higher nursing satisfaction (P < 0.05 and P < 0.01). At discharge, the Glasgow-Blatchford score was declined, the self-rating anxiety scale (SAS) and self-rating depression scale (SDS) scores were declined, the exercise of self-care agency (ESCA) scores were elevated and the Short Form-36 (SF-36) scores were elevated in both groups (P < 0.05). Compared to the control group, the study group had lower Glasgow-Blatchford score, lower SAS and SDS scores, higher ESCA scores and higher SF-36 scores at discharge (P < 0.05).ConclusionGraded nursing based on the Glasgow-Blatchford score can reduce the re-bleeding rate and incidence of adverse reactions, alleviate the anxiety and depression and enhance the self-care ability, quality of life and nursing satisfaction of patients with liver cirrhosis combined with AUGIB.